Problems encountered in the applications of multiple intelligence theory in primary schools in Turkey - Akpinar, Burham; Selim, Erdamar F.; Emrullah, Yilmaz (Elsevier Science Bv, 2010)
In Turkey, serious problems have been encountered in employing MIT in learning-teaching process in primary schools. The aim of this study is to determine the problems experienced in the classroom applications of MIT based on the views of teachers. For this purpose, a likert type scale was applied to a sum of 514 primary school teachers working in the province of Diyarbakir. The data were analyzed using mean, standard deviation, t-test and variance analysis. It was determined that primary school teachers were partly aware of MIT, found it useful and partly took it into consideration while planning the teaching process. Moreover, teachers face a lot of difficulties while making use of MIT. These problems can be listed as follows; inadequate education about the subject, crowded classes, pressure of time, difficulties in evaluation and books and teaching materials that are not compatible with MIT.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Multiple Intelligence Theory; Application Problems of Multiple Intelligence Theory; Teacher Views on Multiple Intelligence Theory; Primary Education and Multiple Intelligence Theory; Problems of Multiple Intelligence Theory in Turkey